2018
DOI: 10.1038/s41598-018-29991-6
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome of Misgurnus anguillicaudatus provides insights into evolution of genus Misgurnus

Abstract: Reconstruction and annotation of transcripts, particularly for a species without reference genome, plays a critical role in gene discovery, investigation of genomic signatures, and genome annotation in the pre-genomic era. This study generated 33,330 full-length transcripts of diploid M. anguillicaudatus using PacBio SMRT Sequencing. A total of 6,918 gene families were identified with two or more isoforms, and 26,683 complete ORFs with an average length of 1,497 bp were detected. Totally, 1,208 high-confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…For example, deciphering highly similar multigene family transcripts from Iso-Seq data with IsoCon has opened the door for gaining a deep understanding of genome evolution and human diseases [19], and the full-length transcripts from the Iso-Seq platform have provided new insight into the extreme metabolism of the ruby-throated hummingbird [20]. Meanwhile, the reconstruction and annotation of fulllength transcripts also plays a critical role in gene discovery, particularly for species with no reference genome, such as the transcript variants involved in the innate immune system in Litopenaeus vannamei [21], gene families with two and more isoforms in Misgurnus anguillicaudatus [22] and transcript diversity in bioactive compound biosynthesis of Astragalus membranaceus [23]. Full-length transcriptome analyses may also drive new innovative progress for understanding the mechanisms of reproduction regulation in sturgeon.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…For example, deciphering highly similar multigene family transcripts from Iso-Seq data with IsoCon has opened the door for gaining a deep understanding of genome evolution and human diseases [19], and the full-length transcripts from the Iso-Seq platform have provided new insight into the extreme metabolism of the ruby-throated hummingbird [20]. Meanwhile, the reconstruction and annotation of fulllength transcripts also plays a critical role in gene discovery, particularly for species with no reference genome, such as the transcript variants involved in the innate immune system in Litopenaeus vannamei [21], gene families with two and more isoforms in Misgurnus anguillicaudatus [22] and transcript diversity in bioactive compound biosynthesis of Astragalus membranaceus [23]. Full-length transcriptome analyses may also drive new innovative progress for understanding the mechanisms of reproduction regulation in sturgeon.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…PacBio SMRT sequencing provides better completeness to the sequencing of both the 5’ and 3’ ends of cDNA molecules; thus, it is a superior strategy for the direct generation of a comprehensive transcriptome with precise AS isoforms and novel genes [3637]. Yi et al identified 33,300 full-length transcripts (transcript N50 of 5234 bp) of Misgurnus anguillicaudatus based on SMRT sequencing, and constructed a transcriptome by performing functional annotations of the non-redundant transcripts with public databases [38]. By sequencing mixed samples of Agasicles hygrophila eggs, larvae, pupae, and adults using PacBio SMRT, Jia and colleagues constructed a transcripotome composed of 28,982 full-length transcripts (transcript N50 of 2331 bp) [5].…”
Section: Discussionmentioning
confidence: 99%
“…The samples can be collected from various tissues (i.e., blood, gill, skin, muscle, liver, spleen, intestine, ovary, testis, kidney, heart, and brain of an animal) [21], or from certain developmental stages (developing rabbit at 21, 49, and 84 days of age) [22]. The high quality of RNA with enough purity and integrity is critical to reduce the amplification cycles required in large-scale PCR and improve the sequencing diversity.…”
Section: Isolation Of Total Rnamentioning
confidence: 99%
“…The high quality of RNA with enough purity and integrity is critical to reduce the amplification cycles required in large-scale PCR and improve the sequencing diversity. RNA extraction is usually done through an easy-spin RNA extraction kit, or RNAiso Pure RNA Isolation kit [20][21][22]. In general, 2-5 μg of total RNA with an RNA integrity number (RIN) greater than 7 is required.…”
Section: Isolation Of Total Rnamentioning
confidence: 99%